De postkoloniale spiegel De Nederlands-Indische letteren herlezen - Honings, Rick; van 't Veer, Coen; Bel, Jacqueline (Leiden University Press, 2021)
The Dutch colonial past in Indonesia has had a major influence on literature. In this edited volume the Dutch East Indies literature is systematically viewed for the first time from a postcolonial perspective. Each essays starts with an introduction about the author's life and his or her relationship with the Dutch East Indies or Indonesia, after which one or more novels are analysed. In addition to famous authors such as Louis Couperus, E. du Perron and Marion Bloem, less well-known writers are also discussed. Recurring points of interest are the representation of the unequal colonial power relations and the European strategies with which the 'Other' was marginalized. 'De postkoloniale spiegel' provides an innovative overview of more than 160 years of Dutch East Indies literary history.